2000
DOI: 10.1097/00001756-200009110-00008
|View full text |Cite
|
Sign up to set email alerts
|

A study of the apparent diffusion coefficient of grey and white matter in human ischaemic stroke

Abstract: We examined whether there was any difference in the value, and temporal evolution, of the apparent diffusion tensor trace (ADC) in acute and subacute grey and white matter lesions. Thirty-seven patients underwent diffusion imaging once (up to 3 days), 15 patients were scanned twice (up to 7 days), and seven patients were scanned three times (up to 14 days) after stroke. Values of the ratio of ischaemic to contralateral ADC (ADCr) were reduced on average by 30% (p<0.001) in the whole hyperintense region up to 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 3 publications
2
8
0
Order By: Relevance
“…Another study of patients during both hyperacute (12-24 h) and acute to subacute (24-72 h) phases of stroke found that both of these patient subgroups exhibited statistically similar declines in ADC av for WM and GM. 42 However, these investigators did find an earlier renormalization of GM lesions (in comparison to WM) as the infarct evolved (although the explanation for this result remains unclear), consistent with observations of other groups. 32 Given the inconsistent results obtained in a number of these recent investigations, it appears that additional studies are needed to better clarify the time course of WM and GM ADC changes during human stroke.…”
Section: Water Diffusion Changes In Human Strokesupporting
confidence: 79%
“…Another study of patients during both hyperacute (12-24 h) and acute to subacute (24-72 h) phases of stroke found that both of these patient subgroups exhibited statistically similar declines in ADC av for WM and GM. 42 However, these investigators did find an earlier renormalization of GM lesions (in comparison to WM) as the infarct evolved (although the explanation for this result remains unclear), consistent with observations of other groups. 32 Given the inconsistent results obtained in a number of these recent investigations, it appears that additional studies are needed to better clarify the time course of WM and GM ADC changes during human stroke.…”
Section: Water Diffusion Changes In Human Strokesupporting
confidence: 79%
“…In contrast, the volume of abnormality can be more readily identified on diffusion-weighted images. The analysis typically ends up becoming a two-step process; first, a volume of abnormal tissue is identified in the DWI, and then the ADC values for that volume are analyzed (10,22,28).…”
Section: Discussionmentioning
confidence: 99%
“…The control is typically assumed to be a homologous region of tissue in the contra-lesional hemisphere. Results are then presented as the ratio of ipsito contra-lesional ADC values (10,22,28,29). While such an approach has proven scientifically fruitful, it significantly degrades the utility of a voxel-based measurement technique by executing the analysis on volumes of interest (VOIs) that are much larger than the original size of the image voxel.…”
Section: Discussionmentioning
confidence: 99%
“…Although ADC and perfusion thresholds have been identified that differentiate between penumbra and other tissue with modest degrees of accuracy, 7,14,15 there is no real difference in ADC thresholds of gray and white matter. 16 Despite lower CBF in white compared with gray matter based on PET studies, there is no evidence to suggest an MTT difference, and it seems reasonable to use an MTT delay of 4 seconds for both compartments. 7 Furthermore, because we used relative MTT values compared with each mirror contralateral voxel rather than absolute values, threshold differences between compartments are eliminated.…”
Section: Koga Et Al Evolution Of Diffusion-perfusion Mismatched Tissuementioning
confidence: 99%